Modulators of the personal and professional threat perception of Olympic athletes in the actual COVID-19 crisis - Clemente-Suárez, V. J.; Fuentes-Garcia, J. P.; de la Vega Marcos, R.; Martinez Patiño, M. J. (Frontiers in Psychology, 2020)
The COVID-19 pandemic is now a major global health issue, affecting world population and high-performance athlete too. The aim of the present research was to analyze the effect of psychological profile, academic schedule, and gender in the perception of personal and professional threat of Olympic and Paralympic athletes facing the 2021 Tokyo Olympiad in the actual COVID-19 crisis. We analyzed in 136 Olympic (26.4 ± 6.2 years) and 39 Paralympic athletes (31.8 ± 9.3 years) academic and sport variables, individual perceptions about COVID-19 crisis, personality, loneliness, psychological inflexibility, and anxiety. Paralympic athletes perceived higher negative impact in their training and performance by the confinement than Olympic athletes (+24.18, p < 0.005, r = 0.60). Neuroticism and psychological inflexibility presented the greatest negative feelings for female athletes (+32.59, p < 0.000, r = 0.13) and the perception that quarantine would negatively affect their sports performance. Finally professional athletes showed lower values in personality tests (Agreeableness factor) about COVID-19 crisis than non-professionals (-40.62, p < 0.012, r = 0.88).